Productivity beyond density: A critique of management models for reindeer pastoralism in Norway - Andrei Marin; Espen Sjaastad; Tor A. Benjaminsen; Mikkel Nils M. Sara; Erik Johan Langfeldt Borgenvik (Pastoralism, 2020)
Abstract The official governance of the reindeer pastoralist system in the north of Norway relies overwhelmingly on one central argument: that in order to maintain a sustainable system, maximum numbers and densities of reindeer, as well as certain herd structures, should be upheld. If these indicators are ignored, the argument goes, the consequences are resource degradation and economic collapse. Even though this argument has been challenged by both researchers and reindeer herders across Fennoscandia, it continues to dominate management policies and practice. Here we set out to investigate the validity of the premise that there is a strong relationship between density and carcass weights over the whole of Finnmark, based on official data. We find that although the relationship is present, its explanatory power is not very strong in a variety of circumstances and propose that it therefore cannot be used to frame important governance policies for the whole system. We also critically reflect on the model’s goal of high productivity per capita of reindeer (high carcass weight). We suggest that productivity per area unit can be at least as relevant as carcass weights and perhaps a better indicator for pastoralist systems in general. For the Finnmark pastoralist system, we argue, a measure of productivity in kilogrammes per square kilometer reveals a different picture: rather than being a failed system marred by suffering animals and low economic returns, reindeer herding in Western Finnmark becomes the most productive in Norway. This shift of focus is likely relevant for other pastoralist systems where governance is premised on similar arguments.